SISTEM INFORMASI GEOGRAFIS SEBARAN PENYAKIT TUBERKULOSIS DI KECAMATAN PANINGGARAN KABUPATEN PEKALONGAN BERBASIS ANDROID - Aslam Fatkhudin (AMIK Jakarta Teknologi Cipta Semarang, 2021)
Tuberculosis is an infectious disease that can infect one person to another caused by the bacterium Mycobacterium tuberculosis. This disease is not only transmitted to people of productive age (15-45), but teenagers or children under 15 years can also be infected with the bacteria. Every year new cases are found in Indonesia, such as in the work area of the Paninggaran Health Center, Paninggaran District. Public Health Centers and Hospitals are health facilities for the community that have the facilities and infrastructure to determine how large the coverage of health figures for the community is. From this analysis, it can be found the obstacles that must be faced, namely how to provide information to the public about the spread of Tuberculosis in Paninggaran District. This is what underlies this research to create an Android-based Geographic Information System application for the distribution of tuberculosis in Paninggaran District with menus that are useful for the wider community and easy to use. The method used in this research is the Waterfall Method. The final result of this study is a